Effects of recovery mode (active vs. passive) on performance during a short high-intensity interval training program: a longitudinal study - Abderrahman, A. B.; Zouhal, H.; Chamari, K.; Thevenet, D.; de Mullenheim, P. -Y.; Gastinger, S.; Tabka, Z.; Prioux, J. (European Journal of Applied Physiology, 2013)
The aim of this longitudinal study was to compare two recovery modes (active vs. passive) during a seven-week high-intensity interval training program (SWHITP) aimed to improve maximal oxygen uptake ( VO2max ), maximal aerobic velocity (MAV), time to exhaustion (t lim) and time spent at a high percentage of VO2max , i.e., above 90 % (t90 V?O2max ) and 95 % (t95 VO2max ) of VO2max . Twenty-four adults were randomly assigned to a control group that did not train (CG, n = 6) and two training groups: intermittent exercise (30 s exercise/30 s recovery) with active (IEA, n = 9) or passive recovery (IEP, n = 9). Before and after seven weeks with (IEA and IEP) or without (CG) high-intensity interval training (HIT) program, all subjects performed a maximal graded test to determine their VO2max and MAV. Subsequently only the subjects of IEA and IEP groups carried out an intermittent exercise test consisting of repeating as long as possible 30 s intensive runs at 105 % of MAV alternating with 30 s active recovery at 50 % of MAV (IEA) or 30 s passive recovery (IEP). Within IEA and IEP, mean t lim and MAV significantly increased between the onset and the end of the SWHITP and no significant difference was found in t90 VO2max and t95 VO2max. Furthermore, before and after the SWHITP, passive recovery allowed a longer t lim for a similar time spent at a high percentage of VO2max. Finally, within IEA, but not in IEP, mean VO2max increased significantly between the onset and the end of the SWHITP both in absolute (p < 0.01) and relative values (p < 0.05). In conclusion, our results showed a significant increase in VO2max after a SWHITP with active recovery in spite of the fact that t lim was significantly longer (more than twice longer) with respect to passive recovery.